2020
DOI: 10.3389/fpsyg.2020.565829
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Visual Art and High Affective Arousal on Heuristic Decision-Making in Consumers

Abstract: In marketing, the use of visual-art-based designs on products or packaging crucially impacts consumers’ decision-making when purchasing. While visual art in product packaging should be designed to induce consumer’s favorable evaluations, it should not evoke excessive affective arousal, because this may lead to the depletion of consumer’s cognitive resources. Thus, consumers may use heuristic decision-making and commit an inadvertent mistake while purchasing. Most existing studies on visual arts in marketing ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 117 publications
(162 reference statements)
0
5
0
1
Order By: Relevance
“…The findings revealed that the product image that was generated with preference EEG-signals had more preference than the product image generated without preference EEG-signals. Kim, et al [ 95 ] conducted an experiment to identify the effect of visual art (e.g., Mondrian’s and Kandinsky’s artworks) on consumers’ preferences, by using EEG. The findings showed that the visual effects induced high emotional arousal, which might promote heuristic decision-making.…”
Section: Resultsmentioning
confidence: 99%
“…The findings revealed that the product image that was generated with preference EEG-signals had more preference than the product image generated without preference EEG-signals. Kim, et al [ 95 ] conducted an experiment to identify the effect of visual art (e.g., Mondrian’s and Kandinsky’s artworks) on consumers’ preferences, by using EEG. The findings showed that the visual effects induced high emotional arousal, which might promote heuristic decision-making.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of reaction times, recorded when participants classified the wine label, also confirms these findings. Research shows that the more we like something, the faster we tend to respond ( Ramsøy, 2014 ; Calvert et al, 2019 ; Kim et al, 2020 ). Our results reveal that participants had shorter RT for the most preferred label CE.…”
Section: Discussionmentioning
confidence: 99%
“…On average, participants took the same amount of time to select IE and IC. Consumer neuroscience research shows that the closer in values two options are, the harder would be for a person to decide between them ( Ramsøy, 2014 ; Kim et al, 2020 ). This might suggest that participants did not have a strong preference for one of the two labels, like for the CE label.…”
Section: Discussionmentioning
confidence: 99%
“…Perception: estas investigaciones profundizan en las medidas de atención en distintos contextos. Entre sus hallazgos se encuentra que la atención visual a los banners en medios sociales presenta niveles bajos de conciencia y escaso o nulo recuerdo posterior (Muñoz-Leiva et al, 2019); el timbre y la sonoridad musical tienen efectos distintos en la construcción de la emoción (valencia y excitación) (Lin et al, 2014) y de la preferencia (Hsu y Chen, 2020); la evaluación de los atributos de los productos es un proceso cognitivo que modula la atención a partir de un procesamiento categórico basado en el juicio de similitud (Wang y Han, 2014) o en la familiaridad cultural (Ma et al, 2019); la atención conjunta incrementa la disposición a pagar más (Madipakkam et al, 2019); los criterios de evaluación en el consumo difieren entre consumidores prosociales (valoran más los costes y los beneficios colectivos) y no prosociales (valoran más el precio) (Medina et al, 2020); o que la elevada excitación afectiva inducida por las artes visuales en los envases de los productos puede conllevar una toma de decisiones heurística en los consumidores (Kim et al, 2020). 7.…”
Section: Figura 1 Evolución Del Número De Artículos Y De Citas En El ...unclassified